2012
DOI: 10.21776/ub.apmba.2012.001.01.4
|View full text |Cite
|
Sign up to set email alerts
|

COLLECTIVE LEADERSHIP: A Case Study of the All Blacks

Abstract: This case study evaluates the development of a formal collective leadership approach by the All Blacks (New Zealand's national men's rugby team) management. The All Blacks have an astonishing 75% winning record in test matches over a hundred year period. This winning ethos is a part of their organizational culture, which has been developed, nurtured and sustained since the inception of the first national team in 1903.The purpose of the study is to develop a greater understanding of the organization and leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In recent years, there has been extensive research concerning organizational culture and sport (e.g., Champ, Nesti, Ronkainen, Tod, & Littlewood, 2020;Donoso-Morales, Bloom, & Caron, 2017;Maitland, Hills, & Rhind, 2015). This work has largely affirmed the interdependent relationship between leadership and culture from a wide range of perspectives, including facilitating highperforming teams (Cole & Martin, 2018;Johnson, Martin, Palmer, Watson, & Ramsey, 2012), enhancing motivational climate (Hodge, Henry, & Smith, 2014), and enriching talent development environments (Henriksen, Stambulova, & Roessler, 2010. Results from a systematic review of organizational culture in sport (Maitland et al, 2015) indicated that among the multitude of definitions and approaches to exploring this topic, the work of Schein (1985Schein ( , 2017 was the most commonly adopted perspective.…”
Section: Organizational Culture In Sportmentioning
confidence: 94%
See 4 more Smart Citations
“…In recent years, there has been extensive research concerning organizational culture and sport (e.g., Champ, Nesti, Ronkainen, Tod, & Littlewood, 2020;Donoso-Morales, Bloom, & Caron, 2017;Maitland, Hills, & Rhind, 2015). This work has largely affirmed the interdependent relationship between leadership and culture from a wide range of perspectives, including facilitating highperforming teams (Cole & Martin, 2018;Johnson, Martin, Palmer, Watson, & Ramsey, 2012), enhancing motivational climate (Hodge, Henry, & Smith, 2014), and enriching talent development environments (Henriksen, Stambulova, & Roessler, 2010. Results from a systematic review of organizational culture in sport (Maitland et al, 2015) indicated that among the multitude of definitions and approaches to exploring this topic, the work of Schein (1985Schein ( , 2017 was the most commonly adopted perspective.…”
Section: Organizational Culture In Sportmentioning
confidence: 94%
“…Hodge et al (2014, p. 60) identified eight factors influencing the motivational climate of the New Zealand All Blacks including "Better People Make Better All Blacks," responsibility and an expectation of excellence. In their qualitative examination of the All Blacks, Johnson et al (2012) highlighted the importance of strong senior leadership and the commitment to total honesty.…”
Section: Organizational Culture In Sportmentioning
confidence: 99%
See 3 more Smart Citations